The influence of relative socioeconomic gap on Spanish children’s performance: evidence from Spain. - Marcenaro-Gutiérrez, Óscar David; Prieto-Latorre, Claudia; López-Agudo, Luis Alejandro (Emerald, 2025)
Purpose. School and out-of-school social environments influence students’ learning process. This research paper aims to study school compositional effects by documenting the influence of students’ relative ranking within the school, in terms of their socioeconomic level and academic performance, on later educational outcomes. Design/methodology/approach. To empirically assess these two influences, this study follows the universe of students attending the third grade in 2015–2016, until the sixth grade, in the Canary Islands. This study exploits changes in students’ relative position in terms of their academic performance and socioeconomic level during primary education. Two different approaches are used to measure students’ relative position: ordinal rank and distance to the average of the class. The identification strategy relies on student fixed effects to go beyond simple correlation. Findings. The results show that being among the students with higher socioeconomic status in school is negatively associated with educational progression, which may be driven by peer effects. The opposite holds true for relative academic rank: being at the top of the school in reading and math positively influences absolute academic performance, which accounts for big-fish-little-pond effects. Additionally, heterogeneous peer effects are identified by school funding. Originality/value. In light of the detrimental impact of social comparisons that often occur in school settings, teachers should actively promote student autonomy in setting personal goals and foster individualised growth, thereby mitigating the influence of social comparisons.
Keywords: Rendimiento académico - Aspectos sociales; Educación - Modelos econométricos; Human capital; Relative socioeconomic status; Relative academic performance; Big-fish-little-pond effects